Experience with host cell protein impurities in biopharmaceuticals. (10th May 2018) - Vanderlaan, Martin; Zhu‐Shimoni, Judith; Lin, Sansan; Gunawan, Feny; Waerner, Thomas; Van Cott, Kevin E.
Abstract : In the 40‐year history of biopharmaceuticals, there have been a few cases where the final products contained residual host cell protein (HCP) impurities at levels high enough to be of concern. This article summarizes the industry experience in these cases where HCP impurities have been presented in public forums and/or published. Regulatory guidance on HCP impurities is limited to advising that products be as pure as practical, with no specified numerical limit because the risk associated with HCP exposure often depends on the clinical setting (route of administration, dose, indication, patient population) and the particular impurity. While the overall safety and purity track record of the industry is excellent, these examples illustrate several important lessons learned about the kinds of HCPs that co‐purify with products (e.g., product homologs, and HCPs that react with product), and the kinds of clinical consequences of HCP impurities (e.g., direct biological activity, immunogenicity, adjuvant). The literature on industry experience with HCP impurities is scattered, and this review draws in to one reference documented examples where the data have been presented in meetings, patents, product inserts, or press releases, in addition to peer‐reviewed journal articles. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:828–837, 2018